1991
DOI: 10.1111/j.1399-6576.1991.tb03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal carbon dioxide removal performed with surface‐heparinized equipment in patients with ARDS

Abstract: To avoid the drawbacks of systemic anticoagulation during prolonged extracorporeal circulation in patients with adult respiratory distress syndrome (ARDS) a heparinization technique has been developed by which partially degraded heparin can be covalently end-point attached to the surface of the equipment constituting the extracorporeal circuit (Carmeda Bio-Active Surface, CBAS) thereby localizing the anticoagulatory effert. Since 1986 we have used extracorporeal circuits and membrane lungs coated with the CBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Following removal of duplicates ( n  = 9), removal of those not meeting screening eligibility criteria ( n  = 118) and full-text exclusions ( n  = 6; see Additional file 3), 14 studies were included in this review (two RCTs and 12 observational studies) [18-31]. …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following removal of duplicates ( n  = 9), removal of those not meeting screening eligibility criteria ( n  = 118) and full-text exclusions ( n  = 6; see Additional file 3), 14 studies were included in this review (two RCTs and 12 observational studies) [18-31]. …”
Section: Reviewmentioning
confidence: 99%
“…In total, 14 studies were included: two RCTs (Table 1) [18,19], and six prospective observational studies [20-25] and six retrospective studies [26-31] (Table 2). The earliest study dated from 1986 and the most recent from 2013.…”
Section: Reviewmentioning
confidence: 99%
“…As a consequence, a longer duration of extracorporeal respiratory support (23 vs 9 days in the Morris et al trial), fewer blood product requirements and the performance of major surgical procedures during ECMO became possible. The heparin-coated membrane lungs, however, had to be changed frequently due to plasma leakage [85][86][87][88][89], exposing the patient to the risks of such maneuvers. Other authors using ECMO with heparinized equipment have also reported prolonged extracorporeal perfusion times without major bleeding complications [79,80].…”
Section: Impact Of Ecmo On Survival Ratesmentioning
confidence: 99%
“…In 1987, Bindslev et al [42] reported the first long-term application of a surface-heparinized extracorporeal circuit in a 44-year-old woman with severe ARDS. Since that time, nearly all European ECMO centres have switched to the surface-heparinized extracorporeal circulation technique, with no or minimal systemic heparinization [10,43]. …”
Section: Historymentioning
confidence: 99%
“…The data support the view that survival rates in both treatment groups followed a positive trend. Data have been taken from [1,5,8,9,10,12,13,14,15,30,31,39,43,55, 56,63,64,91,92,95,96,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130]. …”
Section: Outcome From Extracorporeal Membrane Oxygenationmentioning
confidence: 99%